The Family Caregiving Environment Associates with Adolescent Patients' Severity of Eating Disorder and Interpersonal Problems: A Cross-Sectional Study - Giorgia Baradel; Livio Provenzi; Matteo Chiappedi; Marika Orlandi; Arianna Vecchio; Renato Borgatti; Martina Maria Mensi (MDPI AG, 2023)
The quality of family interactions may be a critical factor for restrictive eating disorders (REDs). Adolescent patients with RED have interpersonal problems that can be inferred by observing their behaviours during family interactions. To date, the assessment of the association among RED severity, interpersonal problems, and patients' interactive behaviours in the family is partially explored. This cross-sectional study aimed to explore how adolescent patients' interactive behaviours observed during the Lausanne Trilogue Play-clinical version (LTPc) were associated with both RED severity and interpersonal problems. Sixty adolescent patients completed the EDI-3 questionnaire to assess RED severity using the Eating Disorder Risk Composite (EDRC) and Interpersonal Problems Composite (IPC) subscales. Moreover, patients and their parents took part in the LTPc, and patients' interactive behaviours were coded as participation, organization, focal attention, and affective contact in all the LTPc four phases. A significant association emerged between patients' interactive behaviours during the LTPc triadic phase and both EDRC and IPC. Better patients' organization and affective contact significantly correlated with lower RED severity and fewer interpersonal problems. These findings suggest that investigating the quality of family relationships and patients' interactive behaviours may contribute to better identifying adolescent patients at risk for more severe conditions.